KEANEKARAGAMAN GASTROPODA DI ZONA LITORAL PANTAI SEURUDONG KABUPATEN ACEH SELATAN - Munirah Mulyati; Kamal, Samsul; Agustina, Elita; Hanim, Nafisah; Ahadi, Rizky (KENANGA : Journal of Biological Sciences and Applied Biology, 2025)
This study aimed to determine the diversity of gastropods in the littoral zone of Seurudong Beach, Sawang District, South Aceh Regency. The research method used a combination of transect and quadrat methods. The research site was divided into 3 different stations. Each station consisted of 3 observation points, with each point placed 4 research plots. Transect lines were drawn from each point vertically from the coast. The transect line used measured 40x10 m, in each transect line there were 4 plots measuring 1x1 m which were placed intermittently with a distance of 10 m between plots. The data were analyzed using the Shannon-Wiener diversity index. A total of 882 gastropod individuals from 24 species and 13 families were found across the three research stations. The diversity of gastropod species found in the littoral zone of Seurudong Beach is in the medium category, with an H' value of 2.473. Environmental measurements recorded the following parameters: temperature (29–31°C), pH (7.9–8.5), and salinity (30–32‰). These values comply with the seawater quality standards established in Decree of the Minister of Environment No. 51 of 2004, indicating favorable and normal ecological conditions at the study site. Keywords :diversity, gastropods, littoral zone, Seurudong Beach